Autodiseño en entornos virtuales : prácticas de autopresentación y visibilización del género en redes sociales digitales - Sartori Green, Tatiana (2022)
The use of self-design in the representation of gender identity in images of user profiles who perceive themselves as non-binaries in the OkCupid social network was analyzed, from a rhetorical-discursive perspective. The images involved in self representations adapt bodies to emerging forms of communication and interaction through devices. Self-design practices acquire a particular dimension in dating social networks ? used to meet sexual, emotional and / or romantic partners? since they promote the transition to face-to-face communication.\nWe seek to reflect on the performative uses of images, and their potential to give visibility to representations of the non-binarix gender. The analysis of the images was structured around the notion of the ethos. The representations revealed a combination and a fluid passage between signs traditionally attributed to the feminine and the masculine, without opting for one or the other model. The approach to self-design as a relational and creative practice of visual communication contributes to thinking about its articulation with gender performativity, the possibility of experimental deployment that it offers, and the potential of certain digital environments for the creation of meaning.